2021
DOI: 10.3390/su132313438
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-Based Approach for the Quantitative Assessment of Soil Quality and Sustainable Agriculture

Abstract: Assessing soil quality is considered one the most important indicators to ensure planned and sustainable use of agricultural lands according to their potential. The current study was carried out to develop a spatial model for the assessment of soil quality, based on four main quality indices, Fertility Index (FI), Physical Index (PI), Chemical Index (CI), and Geomorphologic Index (GI), as well as the Geographic Information System (GIS) and remote sensing data (RS). In addition to the GI, the Normalized Differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…We used the Excel app from Microsoft 365 along with SAS JMP Pro 16.1.0 for graphing and statistical analysis. Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Excel app from Microsoft 365 along with SAS JMP Pro 16.1.0 for graphing and statistical analysis. Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Because healthy vegetation with more chlorophyll reflects higher levels of light in the NIR and absorbs light in the red band, the NDVI distinguishes between areas of thick, healthy plant life vs. unhealthy and/or sparse plant life and has been used to both monitor plant health and drought conditions [49][50][51]. Researchers have shown that NDVI is directly related to the photosyn- Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Miocene and Quaternary deposits are the main geological units [44,45]. The main geomorphologic units in the study area are plains (3453.68 ha), wadi (733 ha), terraces (7149.65 ha), basins (399.27 ha), pavement plain, and reference unit (11064.76 ha) units, according to [46]. Figure 4 shows the three classes of land use and land cover (LULC) highlighted in the investigated area: agriculture, urban, and bare soils.…”
Section: Study Areamentioning
confidence: 99%
“…The sample points number was set at 400, and the iteration number was set at 50,000 as seen in Figures 1 and 5.The selection of the samples (400 points) was based on hydrological and morphometric parameters, i.e., digital elevation model (DEM), slope, curvature, profile curvature, plan curvature, stream power index, slope length, and ISO data classification of the S2A images (Supplementary Materials: Figures S1 and S2) [49], and urban areas were excluded. All soil sample locations were checked in the field; forty-eight locations were chosen to represent different landforms of the study area according to [46] (Figure 6). The soil samples were collected from the study area and transferred to the relevant soil, water, and plant laboratories within the Faculty of Agriculture, Tanta University in accordance with ISO/IEC 17,025:2017 requirements for analysis.…”
Section: Soil Sampling and Laboratory Analysismentioning
confidence: 99%
See 1 more Smart Citation